Thrive - Huffington, Arianna (London Penguin House, 2014)
Arianna Huffington's personal wake-up call came in the form of a broken cheekbone and a nasty gash over her eye -- the result of a fall brought on by exhaustion and lack of sleep. As the cofounder and editor-in-chief of the Huffington Post Media Group -- one of the fastest growing media companies in the world -- celebrated as one of the world's most influential women, and gracing the covers of magazines, she was, by any traditional measure, extraordinarily successful. Yet as she found herself going from brain MRI to CAT scan to echocardiogram, to find out if there was any underlying medical problem beyond exhaustion, she wondered is this really what success feels like?
Includes index
Keywords: Leadership